2015
DOI: 10.1371/journal.pone.0123258
|View full text |Cite
|
Sign up to set email alerts
|

The SKINT1-Like Gene Is Inactivated in Hominoids But Not in All Primate Species: Implications for the Origin of Dendritic Epidermal T Cells

Abstract: Dendritic epidermal T cells, which express an invariant Vγ5Vδ1 T-cell receptor and account for 95% of all resident T cells in the mouse epidermis, play a critical role in skin immune surveillance. These γδ T cells are generated by positive selection in the fetal thymus, after which they migrate to the skin. The development of dendritic epidermal T cells is critically dependent on the Skint1 gene expressed specifically in keratinocytes and thymic epithelial cells, suggesting an indispensable role for Skint1 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 35 publications
(45 reference statements)
0
14
0
Order By: Relevance
“…Skint-1 is the first identified putative selecting element for a major γδ T cell compartment in rodents. Moreover, although all hominoid species appear to have inactivating mutations in the Skint-1- like gene, recent analyses suggest Old World primates do have apparently functional Skint-1 genes, and may possess dendritic epidermal T cell populations ( 39 ). As such, it promises to be of general relevance to other intraepithelial compartments and/or other non-MHC restricted T cells ( 15 , 16 ), in which regard, its biology may inform that of its relative, BTN3A1, which is essential for human peripheral blood γδ T cell recognition of so-called P-Ags ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Skint-1 is the first identified putative selecting element for a major γδ T cell compartment in rodents. Moreover, although all hominoid species appear to have inactivating mutations in the Skint-1- like gene, recent analyses suggest Old World primates do have apparently functional Skint-1 genes, and may possess dendritic epidermal T cell populations ( 39 ). As such, it promises to be of general relevance to other intraepithelial compartments and/or other non-MHC restricted T cells ( 15 , 16 ), in which regard, its biology may inform that of its relative, BTN3A1, which is essential for human peripheral blood γδ T cell recognition of so-called P-Ags ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…They harbor a null mutation in s election and up k eep of in traepithelial T -cells 1 ( Skint1 ), lack canonical Vγ5Vδ1 expressing DETCs. Skint1 , is the founding member of a family ( Skint1-11 ) of butyrophilin-like proteins with containing transmembrane spanning domains and extracellular IgV, and IgC domains (Mohamed et al, 2015). During development, Skint1 is expressed by thymic epithelial cells, promoting functional differentiation of DETC progenitors (Boyden et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The concept of btnl family member-mediated selection of γδ T cells with specific T cell receptor (TCR) heterodimers to tissues has since been extended to mouse Vγ7 γδ T cells localising to the intestine and forming the majority of intraepithelial lymphocytes by interacting with heterodimers of btnl1 and 6 [9]. Whilst humans do not have DETC, most likely due to mutations in the SKINT gene locus [10], conservation of this mechanism was shown through human Vγ4 γδ T cells, which localise to human gut epithelium, where preferentially expressed BTNL3/8 heterodimers induce γδ TCR down-regulation [9]. It has since been confirmed that BTNL3 directly binds to human Vγ4 TCRs via the germ line encoded complementarity determining region (CDR)2, which allows the γδ TCR to additionally bind to antigens via the somatically recombined CDR3 separating tissue selection from antigen recognition [11,12].…”
Section: Introductionmentioning
confidence: 99%